Pemanfaatan Media Online dalam Komunikasi Pariwisata di Pulau Lombok - Kadek Septia Wati; Agus Dwi Putra; I Putu Gede Satria Andika; I Made Puja Artana (Sadharananikarana: Jurnal Ilmiah Komunikasi Hindu, 2022)
This research article aims to investigate the use of online media in tourism communication on Lombok Island. The island of Lombok, one of Indonesia's most popular tourism destinations, is facing increasing competition in promoting its appeal to global tourists. In this ever-evolving digital era, online media has become a very effective tool for reaching a wider audience and influencing travel decisions. This study uses a qualitative approach with data collection methods through in-depth interviews with tourism actors, online media content analysis, and participatory observation. Research informants include tourism stakeholders, tour operators, accommodation managers, and online media industry players on Lombok Island. The results of the study show that the use of online media in tourism communication on Lombok Island has provided significant benefits. First, online media, such as tourism websites, social media, and video sharing platforms, enable tourism actors to promote the attractiveness of Lombok Island to a global audience. Second, online media also facilitate interaction and direct involvement between tourists and tourism actors through online reviews, comments and questions. In conclusion, the use of online media has had a positive impact on tourism communication on Lombok Island. This has helped increase the visibility of Lombok Island in the digital realm, attract tourists, and strengthen the relationship between tourism actors and tourists. In facing increasingly fierce global competition, it is important for tourism actors on Lombok Island to continue to use online media effectively and creatively to promote their destinations to potential tourists.